Screen time exposure and sleep among children with developmental disabilities. (19th April 2018) - Aishworiya, Ramkumar; Kiing, Jennifer SH; Chan, Yiong Huak; Tung, Serena SW; Law, Evelyn
Abstract : Aim: Children with developmental disabilities are at risk of excessive screen time and are more vulnerable to sleep problems. The aim of this study was to determine the extent of screen time use in children with developmental disabilities and its relationship with sleep duration. Methods: Consecutive children aged 6–15 years diagnosed with Diagnostic and Statistical Manual of Mental Disorders, Fourth or Fifth Edition (DSM‐IV or DSM‐5) developmental disabilities were recruited for this study from December 2014 to April 2015. Of those recruited, 87.0% of families gave consent and provided questionnaire information on demographics and child's screen time use and completed the Children's Sleep Habits Questionnaire. Results: Parents of 102 children in a tertiary‐care developmental clinic completed the study. The mean age of children was 10 years, 1 month (standard deviation (SD), 22.7 months). The mean daily total screen time exposure was 2 h, 52.7 min (172.7 min, SD 120.8 min), with a median of 150.0 min. The mean amount of sleep per weekday was 8 h, 23.3 min (SD 64.6 min). Linear regression showed that, for every additional 9.17 min of screen time per day, sleep was reduced by 1 min (β = −0.11, P = 0.04). Older age (β = −0.64, P = 0.02) and living with a single parent (β = −69.29, P = 0.003) were also associated with less sleep. Conclusions: Among children with developmental disabilities, greater daily screen time is associated with lower sleep duration. Older children and those from single‐parent families are at risk of lower sleep duration. Clinicians should routinely ask about screen time exposure and sleep habits in order to provide appropriate anticipatory guidance.